2006
DOI: 10.2519/jospt.2006.36.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of a Femoral Neck/Head Stress Fracture

Abstract: Study Design: Resident's case problem. Background: Identifying stress fractures of the hip can be a challenging differential diagnosis. Pain presentation is not always predictable and radiographs may not show the fracture, especially during its early stages. Hip stress fractures left untreated can displace and necessitate open reduction internal fixation or total hip arthroplasty. Diagnosis: A 70-year-old woman presented to the physical therapy clinic with complaints of right hip pain. She had been evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…While an increase in impact activity can heighten the risk of stress injury development 22,39 , the specific type of athletic activity is important. Russell and Misra demonstrated that elite gymnasts did not have a lower BMD compared with nonexercising peers, whereas running athletes demonstrated significantly lower BMD 24 .…”
Section: Impact Activity Volumementioning
confidence: 99%
See 1 more Smart Citation
“…While an increase in impact activity can heighten the risk of stress injury development 22,39 , the specific type of athletic activity is important. Russell and Misra demonstrated that elite gymnasts did not have a lower BMD compared with nonexercising peers, whereas running athletes demonstrated significantly lower BMD 24 .…”
Section: Impact Activity Volumementioning
confidence: 99%
“…Furthermore, femoroacetabular impingement can cause microtrauma to the femoral neck that could propagate into an overt fracture if subjected to increased load 5,21 . Com-promised proximal femoral structural integrity due to underlying systemic diseases or metabolic disorders can further increase the risk of FNSF development 2,22 .…”
Section: Anatomic Considerationsmentioning
confidence: 99%
“…Femoral neck stress fractures make up 5% of all stress fractures and are often seen in athletes, elderly or those with metabolic bone disease. 1…”
mentioning
confidence: 99%
“…Femoral neck stress fractures make up 5% of all stress fractures and are often seen in athletes, elderly or those with metabolic bone disease. 1 Normal bone formation relies on the delicate equilibrium that exists between bone synthesis and resorption. The accumulation of repetitive eccentric load through the bone with abnormal bone homeostasis leads to nonrepairable microfracturing.…”
mentioning
confidence: 99%